Koherensi Beasiswa Terhadap Motivasi Belajar Mahasiswa Program Studi Pendidikan Ekonomi Universitas Flores - H. Gusti Ma, Stefanus; Masu Lebe, Emerensiana (Program Studi Pendidikan Ekonomi FKIP Universitas Flores, 2024)
This study aims to determine the effect of scholarships on student motivation for the Economic Education Study Program at the University of Flores. The type of research used in this study is an explanation to explain whether there is an influence of the independent variable, namely scholarship, on the dependent variable, namely learning motivation—data collection techniques using questionnaires for primary data and secondary data using documentation studies. The data obtained were analyzed using simple linear analysis. The study results show that scholarships have a significant effect by contributing 24.8 percent to influencing learning motivation in economic education study programs. Therefore, the government and the foundation suggested opening more chances for students to get the scholarship.